Selective green leafy vegetables and their synergistic combination approach as natural anti-diabetic agents: therapeutic potential - Wahyu Haryati Maser; Karthikeyan Venkatachalam; Amit Kumar Rai; Subrahmanyam Karuturi; Sri Charan Bindu Bavisetty; Ali Muhammed Moula Ali (My University, 2023)
Abstract This study examined the antidiabetic potential and antioxidant properties of ten green leafy vegetables (GLVs) using in-vitro tests for α-glucosidase, α-amylase, and lipase inhibition (AGI, AAI, and LPI, respectively). To extract metabolites, 80% ethanol was used, and the resulting crude extract was examined for total phenolic content (TPC) and bioactivities. Of all the samples tested, A. cepa had the highest AGI activity at 595.28 mg ACE/g extract, 25 times greater than the sample with the lowest activity. During the AAI activity, A. fistulosum exhibited the highest inhibition of 36.73 mg ACE/g extract, surpassing all other samples. Meanwhile, P. crispum demonstrated the highest LPI with an inhibition of 31.07%. Among antioxidant activities, DPPH activity was substantial, while metal chelating and FRAP activities were moderate. The results of studies combining A. cepa , A. fistulosum , and A. graveolens L. in equal proportions revealed the most effective combination for inhibiting all enzymes, even though the TPC remained uniform in all combinations. The mechanism of inhibition observed with A. cepa was non-competitive, whereas the combination of A. cepa , A. fistulosum , and A. graveolens L. (combination-1)displayed competitive inhibition, similar to that of acarbose. FTIR was used to identify the functional groups from all the samples. GC-MS results indicated that mannitol, myo-inositol, succinic acid, and propanoic acid were likely responsible for the antidiabetic activity. This research about the potential of GLVs as oral agents for treating T2DM could be critical in managing diabetes and developing functional food to prevent T2DM.
Keywords: Acarbose; Allium fistulosum; Vernonia amygdalina; Functional food; Natural Antidiabetic Agents Studies